2023
DOI: 10.1186/s13690-023-01081-8
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya seroprevalence in population-based studies: a systematic review and meta-analysis

Abstract: Background Seroprevalence studies about chikungunya infection are usually conducted after epidemics to estimate the magnitude of the attack. This study aimed to estimate the seroprevalence of CHIKV by WHO region, considering the periods of introduction of the virus in these regions and its potential to lead to epidemics. Methods We systematically reviewed Medline/Pubmed, Embase, Lilacs, Scopus and Web of Science for original articles published up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
1
1
0
Order By: Relevance
“…For instance, the prevalence of Chikungunya in Itang (Gambella) was approximately triple that of Lare (Gambella). This result is in line with previous studies that revealed the geographical region contributed to the inconsistency in Chikungunya prevalence (23). This is likely due to the extensive distribution and high population density of vectors, particularly in urban centers which are factors that favored their occurrence.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, the prevalence of Chikungunya in Itang (Gambella) was approximately triple that of Lare (Gambella). This result is in line with previous studies that revealed the geographical region contributed to the inconsistency in Chikungunya prevalence (23). This is likely due to the extensive distribution and high population density of vectors, particularly in urban centers which are factors that favored their occurrence.…”
Section: Discussionsupporting
confidence: 92%
“…Among thirty-nine studies conducted on all ages of the population, the seropositivity rate of CHIKV was 30%. The lowest seroprevalence identified was 0.8% in Fiji [ 31 ] and the highest was 95.4% in Laos [ 32 , 33 ]. Moreover, in one seroprevalence study in Thailand in 2014, 30.9% of the Thai population had antibodies against CHIKV [ 34 ].…”
Section: Discussionmentioning
confidence: 99%